Leadership Style of Madrasah Principals in Improving Teacher Performance at MAN Batu Bara - M. Ali Akbar; Muhammad Rifai; Makmur Syukri (Sakura Digital Nusantara, 2026)
Education is a strategic foundation for national development, with madrasahs playing a key role in shaping intellectually competent and morally grounded human resources. The success of a madrasah is closely linked to the quality of learning, which is influenced by teacher performance and, in turn, by the leadership of the madrasah principal. This study aims to (1) describe the leadership style of the principal in improving teacher performance at MAN Batu Bara, (2) examine teacher performance in carrying out professional duties, and (3) identify supporting and inhibiting factors in leadership implementation. This study employed a qualitative descriptive approach and was conducted at MAN Batu Bara. Data were collected through observations and in-depth interviews and analyzed using thematic analysis to gain an in-depth understanding of leadership practices and teacher performance. The findings reveal that the principal’s leadership combines firmness and openness. Firmness is reflected in discipline enforcement and accountability, while openness is evident in participatory communication and teacher involvement. Teacher performance follows a systematic process, including planning, implementation, assessment, and follow-up activities. Although overall performance has improved, disparities remain in instructional quality, use of technology, and implementation of evaluation practices. Supporting factors include effective leadership, organizational structure, positive work culture, supervision, and institutional support. Inhibiting factors involve limited technological access, workload pressures, time constraints, and uneven professional development. In conclusion, effective leadership in madrasahs requires a balance between authority and participation, supported by adequate resources and continuous teacher development.